POLA ASUH ORANG TUA TERHADAP ANAK TUNA NETRA BERPRESTASI USIA SEKOLAH DASAR - Suci Setiarani; Yudhie Suchyadi (Universitas Pakuan, 2018)
Parenting patterns of parenting are the ways and habits that parents do and feel by children, so the pattern will certainly be different on every parent. The aim of this research is to know the parenting pattern of the parent to the blind children with achievement of the blind student with achievement. Sample is taken by looking for SLB-A (blind) in Bogor. This research method is carried out by case study method. Data analysis is an effort done by working with data, organizing data, sorting it into manageable units, synthesizing it, finding and finding patterns, finding what is important and what is learned, and deciding what can be told to others. The result of the research about parenting pattern of the blind children with the achievement of elementary school age shows that the pattern of care is the great potential that make up the achievement of the blind child. Not only one form of parenting, but consists of several parenting patterns, including the pattern of foster democracy, laissez faire care, self-melt parenting, manipulation parenting, parenting patterns, parenting over the role and parenting consultant.Keywords: Patterns of Care, Blind, Achievement.